Puccini's Tosca - Illica, Luigi, 1857-1919 (Opera Journeys Pub., 2005)
A comprehensive guide to Puccini's TOSCA, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 20 music highlight examples.
Based on: La Tosca / Victorien Sardou.
Libretto by Giuseppe Giacosa and Luigi Illica.
Keywords: Puccini, Giacomo, -- 1858-1924. -- Tosca.; Tosca (Puccini, Giacomo); Operas -- Librettos.; Opéras -- Livrets.; MUSIC -- Genres & Styles -- Opera.; Operas -- Librettos